Recognition Award University of Oxford Dept of Engineering - Siegkas, Petros (My University, 2026)
This award is to recognise your outstanding contribution to the Department by undertaking work to allow TIMET to provide an advanced material to Rolls Royce which enabled them to redesign products with a step change improvement, saving money and improving their performance.
Keywords: Business and industry